Clifford the big red dog : the big leaf pile - Page, Josephine; Bridwell, Norman; Durk, Jim (New York : Scholastic, 2000)
Cleo and Clifford cannot resist jumping into the pile of leaves they helped T-Bone gather, but the leaves scatter and they try to get them all back before T-Bone returns.
"Based on the Scholastic book series 'Clifford the big red dog' by Norman Bridwell."
"From the television script 'Leaf of absence' by Scott Guy."
"Cartwheel books."
1.5
K-3
Keywords: Clifford (Fictitious character : Bridwell) -- Fiction; Dogs -- Fiction; Leaves -- Fiction